Ship Propeller Design using Open-Source Codes based on Lifting Line Theory - Sugianto, Erik; Permadi, Niki Veranda Agil; Hasan, Ahmad Darori (Department of Naval Architecture - Diponegoro University, 2025)
The design of a ship's propeller is very important as it directly affects the fuel efficiency, speed, and stability of the ship. Commonly, propellers are designed using expensive commercial software. This research aims to design a ship propeller using open-source code based on lifting line theory and using MATLAB application. The ship data used is a container ship with a length of 397 meters and a width of 56 meters. The propeller design results were propeller performance such as design performance, induced velocity, inflow angle, expanded blade, blade thickness, lift coefficient, performance curve, 2-D and 3-D outlines. A qualitative and quantitative comparison was conducted between a real-world manufactured propeller, a redesigned propeller developed using open-source software (OpenProp), and a commercial design tool (PropCAD). The comparison reveals that while the overall geometry and blade shape of all three propellers are similar, consisting of 6 blades with comparable radial profiles, key differences emerge in the expanded area ratio (EAR), skew angle, and surface modeling quality. The OpenProp design features an EAR of 1.0876 and a high skew angle of 39.9°, indicating an emphasis on hydrodynamic efficiency and cavitation mitigation. In contrast, the PropCAD model presents a slightly lower EAR of 1.077 with a more moderate skew angle of 20.5°, offering a balanced compromise between performance and manufacturability. This distinction highlights a potential optimization opportunity and demonstrates the capability of the open-source design approach to approximate real-world propeller characteristics with high fidelity, while also offering flexibility for further refinement. In summary, the findings suggest that the open-source design approach can approximate real-world propeller characteristics with high fidelity and provide flexibility for iterative optimization.